Incidence of Herpes Zoster and Persistent Post-Zoster Pain in Adults With or Without Diabetes in the United States - Suaya, Jose A. (Open Forum Infect Dis, 2014)
BACKGROUND:  This study was designed to assess the association between diabetes and herpes zoster (HZ) and persistent post-zoster pain (PPZP). METHODS:  We used a United States-based, 2005–2009 retrospective observational study of medical and pharmacy claims from adults in 3 large national databases. Incidence rate ratios were used to compare HZ incidence by diabetes status. Multivariate regressions assessed the age and sex-adjusted risk of diabetes on HZ and PPZP as a function of immune competence. National projections of HZ and PPZP cases were obtained. RESULTS:  Among 51 million enrollees (∼88 million person-years [PYs] at risk), we identified 420 515 HZ cases. Patients with diabetes represented 8.7% of the PYs analyzed but accounted for 14.5% of the HZ cases and 20.3% of the PPZP cases. The crude incidence of HZ was 78% higher (7.96 vs 4.48 cases/1000 PY; P < .01) and the rate of PPZP was 50% higher (5.97% vs 3.93%; P < .01) in individuals with diabetes than without. Individuals with diabetes had 45% higher adjusted risk of HZ (hazard ratio [HR] = 1.45; 95% confidence intervals [CIs], 1.43–1.46) and 18% higher adjusted odds of PPZP (odds ratio = 1.18; 95% CI, 1.13–1.24). The risk of HZ associated with diabetes among immune-compromised individuals was weaker (HR = 1.10; 95% CI, 1.07–1.14) and the risk of PPZP was no longer significant. Every year, approximately 1.2 million HZ cases occur in US adults, 13% of these occur in individuals with diabetes. CONCLUSIONS:  Diabetes is a risk factor for HZ and PPZP in the US adult population. This association is stronger in immune-competent individuals.